The Effects of Cryotherapy on Knee Joint Position Sense and Force Production Sense in Healthy Individuals - Furmanek, Mariusz P. (J Hum Kinet, 2018)
The proprioceptive information received from mechanoreceptors is potentially responsible for controlling the joint position and force differentiation. However, it is unknown whether cryotherapy influences this complex mechanism. Previously reported results are not universally conclusive and sometimes even contradictory. The main objective of this study was to investigate the impact of local cryotherapy on knee joint position sense (JPS) and force production sense (FPS). The study group consisted of 55 healthy participants (age: 21 ± 2 years, body height: 171.2 ± 9 cm, body mass: 63.3 ± 12 kg, BMI: 21.5 ± 2.6). Local cooling was achieved with the use of gel-packs cooled to -2 ± 2.5°C and applied simultaneously over the knee joint and the quadriceps femoris muscle for 20 minutes. JPS and FPS were evaluated using the Biodex System 4 Pro apparatus. Repeated measures analysis of variance (ANOVA) did not show any statistically significant changes of the JPS and FPS under application of cryotherapy for all analyzed variables: the JPS’s absolute error (p = 0.976), its relative error (p = 0.295), and its variable error (p = 0.489); the FPS’s absolute error (p = 0.688), its relative error (p = 0.193), and its variable error (p = 0.123). The results indicate that local cooling does not affect proprioceptive acuity of the healthy knee joint. They also suggest that local limited cooling before physical activity at low velocity did not present health or injury risk in this particular study group.